Study of potentially toxic elements uptake into organs of Quercus spp. from copper deposits in Slovakia, Italy and Portugal - Andráš, Peter (2021)
ABSTRACT: The article is focused on the application of Energy dispersive micro X-ray fuorescence spectroscopy as a specifc method to determine the contents of potentially toxic elements and its spread in plant tissues. As a model species, Quercus spp. were selected. In order to compare the obtained results with previous research, four well-described abandoned Cu-deposits were selected for sampling: Ľubietová (Slovakia), Libiola and Caporciano (Italy), and São Domingos (Portugal). The results of micro X-ray fuorescence spectrometry confrm the irregular contamination of Quercus spp. by potentially toxic elements. The level of contamination is the highest predominantly in the root cortex, where is also the highest Ca contents (with exception of São Domingos). At Ľubietová and Caporciano, high Ni content was described in branches cortex, in branches mesoderm also Fe, Cu and Zn. At the same time, the inhibition infuence of Ca was also confrmed regarding the input of these elements into plants.